2020
DOI: 10.1371/journal.pcbi.1006919
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling and taxis mechanisms regulate early stage angiogenesis: A mathematical and computational model

Abstract: During angiogenesis, new blood vessels sprout and grow from existing ones. This process plays a crucial role in organ development and repair, in wound healing and in numerous pathological processes such as cancer progression or diabetes. Here, we present a mathematical model of early stage angiogenesis that permits exploration of the relative importance of mechanical, chemical and cellular cues. Endothelial cells proliferate and move over an extracellular matrix by following external gradients of Vessel Endoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 89 publications
0
43
0
Order By: Relevance
“…Angiogenic sprouting has been extensively studied from a theoretical modelling perspective in numerous physiological and pathological contexts, including tumour growth [ 10 , 16 33 ]. Many models [ 18 20 , 22 , 24 28 , 32 ] fall within the so-called snail-trail paradigm [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenic sprouting has been extensively studied from a theoretical modelling perspective in numerous physiological and pathological contexts, including tumour growth [ 10 , 16 33 ]. Many models [ 18 20 , 22 , 24 28 , 32 ] fall within the so-called snail-trail paradigm [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the value of our results, e.g, for studies of metastatic cancer, future works may add cellular mechanisms such as Notch signaling dynamics [ 46 ], models of epithelial/mesenchymal transition and cancer stem cell formation [ 47 , 48 ] to our vertex model. This venue has been successfully followed in studies of angiogenesis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promising mechanisms include Notch signaling pathways [ 46 ] and models of the epithelial-mesenchymal transition and cancer stem cell formation [ 47 , 48 ]. Incorporating these cellular mechanisms to our vertex model may pave the way to future progress in this area, much as incorporating the Notch signaling pathway to cellular Potts models helps understanding many aspects of angiogenesis [ 49 ]. Understanding precise biochemical mechanisms influencing cell-cell contact and confluent cellular tissue may help develop therapies for metastatic cancers [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent mathematical model of early stage angiogenesis explores the relative importance of mechanical, chemical and cellular cues. Endothelial cells proliferate and move over an extracellular matrix by following external gradients of VEGF, adhesion and stiffness, which are modeled using a cellular Potts model with a finite element description of elasticity [142]. As an early attempt, Bentley et al proposed a hierarchical agent-based model simulating a suggested feedback loop that links VEGF-A tip cell induction with delta-like 4 (Dll4)/notch-mediated lateral inhibition [143].…”
Section: Cell Dynamics Modelsmentioning
confidence: 99%